Riflessi di storia universitaria e norme di disciplinamento del clero in area subalpina da una fonte canonistica spagnola (1435 ca.) - Paolo Rosso (Rivista di Storia dell'Università di Torino)
The treatise for confessors Speculum peccatoris, confessoris simul et praedicatoris in materia restitutionis seu satisfactionis, preserved in manuscript 37 of the Biblioteca de la Real Colegiata de San Isidoro de León, offers valuable insights into the social and religious history of the Subalpine area in the first half of the fifteenth century. The author, most likely the Spanish cleric Gómez González, gathered this information during his stay in Piedmont around 1435. This essay presents several cases of abuses committed by both laypeople and members of the clergy, as described in the Speculum. These cases include references to the University of Turin, which at the time had been temporarily relocated to Chieri (1427-1434) and to Savigliano (1434-1436). All references to the University of Turin concern issues related to the management of ecclesiastical benefices and provide information on faculty members, teaching practices in canon law at the Studium generale, and the involvement of local university doctors of canon law in judicial procedures of ecclesiastical courts.